2008
DOI: 10.1086/591125
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Polar Jets as Precursors of Polar Plume Formation

Abstract: Observations from the Hinode/XRT telescope and STEREO/SECCHI/EUVI are utilized to study polar coronal jets and plumes. The study focuses on the temporal evolution of both structures and their relationship. The data sample, spanning 2007 April 7-8, shows that over 90% of the 28 observed jet events are associated with polar plumes. EUV images (STEREO/SECCHI) show plume haze rising from the location of approximately 70% of the polar X-ray (Hinode/XRT) and EUV jets, with the plume haze appearing minutes to hours a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 19 publications
8
77
0
Order By: Relevance
“…They further discovered that the polar region is also covered with ubiquitous horizontal fields, which agrees with the work done by who found ubiquitous and dynamic horizontal fields in the quiet Sun over the solar disk (see also Lites et al, 2008). Much effort has also been made to link dynamics of the magnetic field elements and coronal phenomena at high latitude, such as plumes, X-ray bright points, and X-ray jets (e.g., Deforest et al, 1997;Wang, 1998;Cirtain et al, 2007;Raouafi et al, 2008). The nature of the solar polar regions is still an important topic that deserves further investigation.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…They further discovered that the polar region is also covered with ubiquitous horizontal fields, which agrees with the work done by who found ubiquitous and dynamic horizontal fields in the quiet Sun over the solar disk (see also Lites et al, 2008). Much effort has also been made to link dynamics of the magnetic field elements and coronal phenomena at high latitude, such as plumes, X-ray bright points, and X-ray jets (e.g., Deforest et al, 1997;Wang, 1998;Cirtain et al, 2007;Raouafi et al, 2008). The nature of the solar polar regions is still an important topic that deserves further investigation.…”
Section: Introductionsupporting
confidence: 73%
“…Based on the Hinode observation, Tsuneta (2009) estimated the lifetime of the elements to be within 10 to 15 h. Thus, it is useful to give a statistical measurement of the lifetime of the magnetic field elements on the polar regions. The solar rotation rate at high latitude has also been measured using various methods, such as spectroscopic (e.g., Howard and Harvey, 1970;Becker, 1978), image cross-correlation (e.g., Cram, Durney, and Guenther, 1983;Snodgrass, 1983;Strous and Simon, 1998;Meunier, 2005), and element tracking (e.g., Howard, 1978;Zhang, Zirin, and Marquette, 1997;Deng, Wang, and Harvey, 1999;Benevolenskaya, 2007). In this paper, we measure the magnetic field element lifetime and rotation rate at high latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Coronal X-ray jets, on the other hand, are sufficiently isolated that their solar wind signature should be clearly measurable. Polar plumes are observationally linked to jets (Raouafi et al 2008) and are visible in coronagraph images out to at least 30R s (De Forest et al 2001). Variation in e-strahl and PAD correlated with Type-III radio emission (prompt radio emission from beams of electrons escaping from the corona) will determine if SPP is sampling the open flux tube that contains the jet material.…”
Section: Sources Of the Solar Windmentioning
confidence: 99%
“…Wang and Sheeley (1995) and Wang (1998) proposed that plumes are produced by the reconnection of emerging mixed-polarity fields with previously existing unipolar fields. Raouafi et al (2008) reported that most of the studied coronal jets in polar regions are generally followed by plumes. The authors pointed out the common feature shared by plumes and jets: a mixedpolarity field area where their footpoints are located.…”
Section: Polar Plumesmentioning
confidence: 99%